Exploring ESL students’ writing development in the higher education ODL programme / Siti Soraya Lin Abdullah Kamal - Abdullah Kamal, Siti Soraya Lin (Universiti Teknologi MARA, Kedah, 2024)
Limited research investigates the experiences of ESL students developing writing proficiency in Open and Distance Learning (ODL) settings at the higher education level in Malaysia. This study addresses this gap by exploring ESL students' perceptions and experiences regarding confidence, challenges, and strategies for writing development in ODL programmes. Utilizing qualitative methods, the research examines how ODL environments influence student experiences. Interviews with 30 ODL students were conducted and analyzed using a thematic approach. Findings reveal diverse confidence levels linked to factors like family background, English exposure, and the learning environment. Students also face challenges in grammar, vocabulary, and formal writing tasks. To overcome these obstacles, students employ strategies such as extensive reading, engaging with English media, seeking feedback, and persistent practice. The study highlights the global significance of English and the impact of cultural and family contexts on ESL writing development. By recognizing the interconnected ecological factors shaping students' writing journeys, ODL institutions can develop tailored support programmes and promote cultural inclusivity, ultimately enhancing ESL students' writing development in ODL contexts.